2021
DOI: 10.1186/s12951-021-01180-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined integrin αvβ3 and lactoferrin receptor targeted docetaxel liposomes enhance the brain targeting effect and anti-glioma effect

Abstract: The integrin αvβ3 receptor and Lactoferrin receptor (LfR) are over-expressed in both cerebral microvascular endothelial cells and glioma cells. RGD tripeptide and Lf can specifically bind with integrin αvβ3 receptor and LfR, respectively. In our study, RGD and Lf dual-modified liposomes loaded with docetaxel (DTX) were designed to enhance the brain targeting effect and treatment of glioma. Our in vitro studies have shown that RGD-Lf-LP can significantly enhance the cellular uptake of U87 MG cells and human cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
(72 reference statements)
0
27
0
Order By: Relevance
“…For instance, lactoferrin (Lf), a multifunctional glycoprotein, is only expressed in brain capillaries. Qi et al ( 174 ) indicated that a targeted delivery system modified by Lf is able to markedly improve the ability of docetaxel liposomes to cross the BBB and enhance brain targeting effects, demonstrating its potential as a promising chemotherapeutic drug delivery system for glioblastoma. Angiopep-2 (Ang) is able to specifically bind to receptor-related protein 1 (LRP-1), which is highly expressed on the glioma cell membrane.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…For instance, lactoferrin (Lf), a multifunctional glycoprotein, is only expressed in brain capillaries. Qi et al ( 174 ) indicated that a targeted delivery system modified by Lf is able to markedly improve the ability of docetaxel liposomes to cross the BBB and enhance brain targeting effects, demonstrating its potential as a promising chemotherapeutic drug delivery system for glioblastoma. Angiopep-2 (Ang) is able to specifically bind to receptor-related protein 1 (LRP-1), which is highly expressed on the glioma cell membrane.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Lactoferrin (Lf) is a natural protein, 80 kDa glycoprotein, and belongs to the transferrin family [ 153 , 154 ]. Lactoferrin-based liposomes have been used as ligands of the lactoferrin receptor (LfR) to reach some cancers, such as liver and brain tumors [ 155 , 156 ], and as ligands of other overexpressed receptors [ 157 , 158 ]. Several recent studies demonstrated that Lf is a potential liposome ligand for targeting numerous receptors overexpressed in tumors, improving anticancer activity, increasing cellular uptake and simultaneously lowering side effects.…”
Section: Nanocarriers For Targeted Cancer Therapymentioning
confidence: 99%
“…The modification of two different ligands may lead to better and controllable lesion site selectivity (Gao, 2016; Ruan et al, 2021). Several peptides or proteins were utilized in this field, including ApoA‐I, angiopep‐2, T7, and lactoferrin for BBB overcoming and NL4, CD133 antibody, RGD, NGR, and D A7R for targeting lesion site (Fu et al, 2019; Kim, Shin, & Kim, 2018; Qi et al, 2021; Zhang, Gu, et al, 2017; Zhang, Zhai, et al, 2017). Notably, although the dual targeting delivery system enables precise multiple targeting capabilities, the in vivo process and clinical translation of the delivery system are limited due to the complex modification process.…”
Section: Bbb Alteration In Brain Diseases and Targeting Delivery Stra...mentioning
confidence: 99%